2017
DOI: 10.1093/cid/cix472
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Zika Virus Disease Severity, Virus Load, Prior Dengue Antibodies, and Their Relationship to Birth Outcomes

Abstract: Congenital ZIKV syndrome does not appear to be associated with maternal disease severity, ZIKV-RNA load at time of infection or existence of prior dengue antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 29 publications
3
81
1
1
Order By: Relevance
“…In Haiti, in contrast to other studies that relied on serologic assays, we performed actual viral cultures on a majority of case patients; findings further underscored the extent of coinfections [19], and resulted in the identification of "unexpected" viruses, such as ZIKV and MAYV. It remains to be seen what impact this mix of infections has on host susceptibility and disease occurrence and severity [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In Haiti, in contrast to other studies that relied on serologic assays, we performed actual viral cultures on a majority of case patients; findings further underscored the extent of coinfections [19], and resulted in the identification of "unexpected" viruses, such as ZIKV and MAYV. It remains to be seen what impact this mix of infections has on host susceptibility and disease occurrence and severity [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The exact 281 threshold viremia that results in productive mosquito infection remains unknown, but a recent 282 study used artificial membrane feeding to establish a minimum infective dose of 4.2 log 10 283 PFU/ml for susceptibility in mosquitoes 42 . It should be noted that viral loads in macaque plasma 284 resemble those reported in humans in endemic areas 32,[43][44][45]45,46 . Furthermore, the first clinical 285 description of a patient suffering from Zika fever was reported in 1956, and was based on a 286 ZIKV infection experimentally induced in a human volunteer 47 .…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 64%
“…In sum, it is impossible to replicate the 44 biological, physiological, and mechanical phenomena of mosquito feeding and/or probing using 45 a needle. 46 The amount of ZIKV inoculated by mosquitoes into a host is not known. In the majority of our 47 previous studies we used an inoculum dose of 1 x 10 4 PFU injected subcutaneously (sc) 1,2,24 , 48 which we chose as a dose likely to be delivered by a ZIKV-infected mosquito.…”
Section: Introduction 18mentioning
confidence: 99%
“…149 As discussed above, clinical correlation of cross-flavivirus reactivity is as yet unresolved. There is no epidemiologic data to suggest that the current Zika virus epidemic has increased the risk for DHF and as presented above, one study in pregnant females showed no evidence of differences in disease severity related to prior DENV seropositivity 137 and other studies have shown that prior DENV serotype I infection may be associated with increased neutralizing antibody titers 134 that could result in greater protection.…”
Section: Zika Virus Vaccine Developmentmentioning
confidence: 96%
“…A study of 131 PCR-positive pregnant women found no correlation (p D 0.667) between the presence of prior DENV antibodies and disease severity, and with no relationship between Zika viral load and adverse outcomes such as fetal loss. 137 Thus, the clinical implication of prior flavivirus immunity remains unanswered.…”
Section: Laboratory Correlates and Immunology Of Zika Virus Infectionmentioning
confidence: 99%